2019
DOI: 10.5222/iksstd.2019.20982
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Diagnosis in Developmental Dysplasia of the Hip (I)

Abstract: Gelişimsel kalça displazisi (GKD), kalça ekleminin gelişimi sırasında proksimal femur ile asetabulumun anatomik ilişkisinin bozulduğu bir hastalıktır. Asetabuler displazi, subluksasyon ve dislokasyon süreçlerini içerir. Tanıda risk faktörlerinin değerlendirilmesi, fizik muayene ve radyolojik görüntüleme yöntemleri ciddi öneme sahiptir. Tanı ne kadar gecikirse, asetabular ve femoral remodelizasyon potansiyeli o kadar azalır. GKD yönetiminde en önemli basamağın erken tanı olduğu tartışılmaz bir gerçektir. Bu ned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…D evelopmental hip dysplasia (DDH) is a vigorous disease in which the structures that compose the hip joint, which are normal during their intrauterine formation, subsequently and for various reasons show structural deterioration [1]. The main goal in DDH treatment is to ensure the concentric reduction of the hip joint as soon as possible and to provide interaction between the proximal femur and the acetabulum [2]. It has been reported that the acetabulum has the ability to develop over many years when appropriate contact is provided between the femoral head and acetabulum [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…D evelopmental hip dysplasia (DDH) is a vigorous disease in which the structures that compose the hip joint, which are normal during their intrauterine formation, subsequently and for various reasons show structural deterioration [1]. The main goal in DDH treatment is to ensure the concentric reduction of the hip joint as soon as possible and to provide interaction between the proximal femur and the acetabulum [2]. It has been reported that the acetabulum has the ability to develop over many years when appropriate contact is provided between the femoral head and acetabulum [3].…”
Section: Introductionmentioning
confidence: 99%
“…As the diagnosis is delayed, the joint remodelling ability and treatment success decreases, causing complications, and the risk of developing degenerative joint disease increases. The significance of providing the patient with a lifelong, painless and functional hip joint is early diagnosis and treatment [2].…”
Section: Introductionmentioning
confidence: 99%
“…Serious studies conducted within the last 10 years in our country undoubtedly promise positive results for the early diagnosis and treatment of this disease (2). However, it is known that setbacks in the diagnosis and treatment of the disease will irreversibly affect the future of the individual and also cause serious damage to the country's economy (7). Setbacks in the diagnosis stage reduce the chance of early treatment of the patients.…”
Section: Introductionmentioning
confidence: 99%